Effectiveness of Angiotensin Converting Enzyme Inhibitors and Beta-Blockers in Reducing Mortality in Patients with Congestive Heart Failure - Andi Alfiyah Az-Zahro Iswahyudi; Wisudawan; Ardiyanto (Newinera Publisher, 2026)
CHF is a chronic and progressive cardiovascular disease with high morbidity, frequent hospitalization and a high mortality rate, especially for individuals with HFREF. The purpose of this study is to assess the efficacy of angiotensin converting enzyme inhibitors and beta blockers in the reduction of mortality in congestive heart failure patients especially in terms of the neurohormonal modulation and long-term clinical results. In this study, a narrative literature review design was used to obtain secondary data from national and international journals, textbooks, ClinicalKey, ScienceDirect, PubMed, Google Scholar, scientific websites of publishers, and other relevant scientific sources. The existing literature focused on studies from 2015 to 2026, with the exception of landmark studies from the past that provided foundational evidence relevant to heart failure pharmacotherapy. The results suggest that ACE inhibitors and beta blockers are associated with consistently lower mortality, hospitalization rate and clinical stability, particularly in those with heart failure with reduced EF. Angiotensin converting enzyme inhibitors (ACE inhibitors) can help decrease the harmful effects of activation of the renin angiotensin aldosterone system (RAAS) while beta blockers can help to reduce excessive sympathetic nervous system activity. They both have complementary neurohormonal control and can have a wider clinical effect than monotherapy, if used appropriately. The therapeutic efficacy, however, is not consistent in every patient, and may be affected by the level of ejection fraction (EF), age, comorbidities, disease severity, drug tolerance, dose optimization, and adherence to therapy. This review demonstrates that ACE inhibitors and beta blockers are still employed by patients with CHF and are still considered critical components of guideline directed pharmacologic therapy, especially in those patients with reduced EF.